Teacher's Reflective Thinking Model in Overcoming Students' Problems at Schools Through Digital Communication - Suhifatullah, M. I.; Darmojo, Hardjito S (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to find "Teachers' Reflective Thinking Model in Overcoming Student Problems at School Through Digital Communication". This study is considered important considering that there are still many student problems at school that are resolved by teachers in a reactive and spontaneous manner, without involving a reflective thinking approach. So instead of being able to resolve student problems, it can actually create new problems. This study uses a research and development method, so that it focuses more on the activity of developing a product through testing to see its effectiveness and usefulness before being socialized. The subjects of this research were teachers at SMP Negeri 1 Kedung Waringin, Bekasi Regency. Data collection through interviews, surveys, questionnaires and literature studies. Data analysis techniques used quantitative descriptive analysis. The results of the study showed that the teacher's reflective thinking model in overcoming student problems through digital communication is very feasible to use or can be a reference for teachers related to the stages in overcoming student problems at school. Through this model, the teacher's attitude can be more controlled and empathetic in dealing with student problems, so that they are able to take more controlled, measurable and effective actions.